Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content: 1. The degree to which primary grade teachers use mind maps in teaching and the obstacles to use from the point of view of female educational supervisors in the city of Mecca Ms. Hala Khaled Al-Qathami ,Prof. Mohammad Ahmed Manasrah 2. Teaching school geography according to the standards-based approach: An analytical study of The American experience and its challenges Ms. Kamil Wafaa, Prof. Mohamed Kafssi , Prof. Abdelali Soulali 3. The Effectiveness of Using Animated Infographic Technology in Developing Visual Thinking Skills of Seventh Grade Students in science course Ms. Bashayer Mubarak Al-Harthi, Ms. Shahid Abdullah Al-Ghamdi, Co-Prof. Fadwa Yassin Filmban 4. Between Local Perspectives and Theories: A Study of Derivative Teaching Practices in Secondary Schools in Palestine Dr. Saja Akram Fares 5. The effect of using the Geometry Pad on geometric achievement and revealing geometric fallacies among fifth-grade primary school students Dr. Mustafa Raad Abd Ulrasool Al-Saadi 6. Female educational supervisors and problems in the educational field Ms. Hessa Jahz Zaben Al-Tarisi, Prof. Waleed Ibrahim Ali Al-Abiky 7. Using L1 in Teaching Vocabulary to Low-Proficiency-Level Students in The University College of Khafji for Female Students Dr. Abeer Hamed Aldhefeir